INFORMATION AND COMMUNICATION TECHNOLOGIES ICT AND THEIR INFLUENCE ON RURAL EDUCATION - Carlos Hernando Quintero Calvo; Harvey Orlando Prado Chinchilla (LÍNEA IMAGINARIA, 2025)
New technologies have a significant influence on the different areas of social performance, shaping the daily development of individuals. Their proliferation has been such that they have permeated all spaces of people, with the educational field being one of the most invaded. Nowadays it is difficult to carry out a class day based only on the use of traditional or basic resources such as the board or guides, on the contrary, the use of Information and Communication Technologies (ICT) is now necessary; however, in rural areas the use of ICT is more complicated than expected, the causes for this reality are diverse, but even so they must be linked in these areas. This paper aims to offer a relationship between ICT and education in rural areas, including the influence and changes that they can cause, highlighting the possible impact that they could have on the development of the educational fact, all of this from a review of documents supported by the hermeneutics method for their analysis. So it is concluded that reality shows an inconsistency regarding the implementation of ICT in the educational field, since in the urban environment these instruments are taking over the classes, in the rural context they are in many cases not being used, which is why they are not generating the same impact.